The Effect of Argument-Driven Inquiry (ADI) on Argumentation Skills and Students' Concept Mastering of Human Excretory System Materials - Vita Riyanti; Yanti Hamdiyati; Widi Purwianingsih (Journal of Science Learning, 2023)
This study aims to determine the effect of the Argument-Driven Inquiry (ADI) learning model on students' argumentation skills and mastery of concepts in human excretory system material, especially in the sub-material of kidney disorders. The research method used quasi-experimental with a group pretest-posttest design. The sample of this research was second-grade MIPA students in one of the high schools in Bandung, which consisted of 29 students in the experimental class and 25 students in the control class. The purposive sampling technique did the sampling. The study used some instruments, which consisted of a test of argumentation skills in the form of essay questions, an exam of mastery of concepts in the form of multiple choice, and a questionnaire on student responses to learning using the ADI learning model. The results showed that the ADI learning model had a more significant effect on argumentation skills in the experimental class than in the control class, with a significance value of 0.019. The quality of students' argumentation was at level 3. However, the ADI learning model did not significantly affect students' mastery of concepts in the excretory system material because a significant difference was not found between the pretest and posttest data in both research classes. Student response data shows students respond completely well to applying the ADI learning model. Therefore, the ADI learning model is recommended for biology teachers to improve students' argumentation skills and concepts mastery in other biological materials.